2013
DOI: 10.26618/ejpbi.v2i1.784
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Students’ Reading Comprehension Using Tiered Tasks Strategy

Abstract: This research aimed to explain the students’ achievement in literal reading comprehension using Tiered Tasks Strategy, as well as to explain the students’ achievement in interpretative reading comprehension using Tiered Tasks Strategy. This research used Classroom Action Research and applied to cycles in the application, they are cycle 1 and 2 with 4 meetings in every cycle. The improvement of students’ ability to write narrative text using Tiered Tasks Strategy had an effective effect. The researcher found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The findings in the present study demonstrated a success in using tiered reading instruction to enhance reading comprehension of EFL secondary school students in Thailand. The positive effects found in the present study are consistent with previous findings (e.g., Aliakbari & Haghighi, 2014;Natsir & Asrawiah, 2013;Pasuy Pedroza & Mendieta Aguilar, 2013). The improvement of the reading comprehension, especially the two high levels of comprehension, suggests that all students, regardless of their existing reading ability, must have received adequate support during the instruction (cf.…”
Section: Journal Of Educational Issuessupporting
confidence: 93%
See 4 more Smart Citations
“…The findings in the present study demonstrated a success in using tiered reading instruction to enhance reading comprehension of EFL secondary school students in Thailand. The positive effects found in the present study are consistent with previous findings (e.g., Aliakbari & Haghighi, 2014;Natsir & Asrawiah, 2013;Pasuy Pedroza & Mendieta Aguilar, 2013). The improvement of the reading comprehension, especially the two high levels of comprehension, suggests that all students, regardless of their existing reading ability, must have received adequate support during the instruction (cf.…”
Section: Journal Of Educational Issuessupporting
confidence: 93%
“…Gregory, 2011;Tomlinson, 2000). This lends support to the argument that tiered instruction can enhance the learning of students in mixed-ability classrooms (see also Aliakbari & Haghighi, 2014;Amkham & Chinokul, 2010;García Fonseca & Casallas Gordillo, 2016;Magableh & Abdullah, 2020;Natsir & Asrawiah, 2013;Pasuy Pedroza & Mendieta Aguilar, 2013;Pourdana & Shahpouri Rad, 2017;Suthipiyapathra et al, 2019).…”
Section: Journal Of Educational Issuesmentioning
confidence: 52%
See 3 more Smart Citations